2019
DOI: 10.30554/archmed.20.1.3468.2020
|View full text |Cite
|
Sign up to set email alerts
|

Variables demográficas que predicen el intento de suicidio en población local española

Abstract: Objetivo: esta investigación pretende estudiar las variables epidemiológicas relacionadas con la tentativa y el reintento de suicidio y si entre ellas los trastornos de ansiedad son importantes. En la conducta suicida existen fases previas menos investigadas que son altamente predictivas del suicidio consumado, como son los intentos o reintentos de suicidio.  Materiales y métodos: consistió en recoger datos digitales en los servicios de urgencias hospitalarias durante 26 meses. Resultados: los resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…A revisão narrativa da literatura é apropriada para descrever e discutir o desenvolvimento ou o estado da arte de um determinado assunto, do ponto de vista teórico ou contextual. Constitui-se, basicamente, de análise da literatura publicada em livros, artigos de revistas impressas e/ou eletrônicas, na interpretação e análise crítica pessoal do autor (ROTHER, 2007).…”
Section: Métodosunclassified
“…A revisão narrativa da literatura é apropriada para descrever e discutir o desenvolvimento ou o estado da arte de um determinado assunto, do ponto de vista teórico ou contextual. Constitui-se, basicamente, de análise da literatura publicada em livros, artigos de revistas impressas e/ou eletrônicas, na interpretação e análise crítica pessoal do autor (ROTHER, 2007).…”
Section: Métodosunclassified
“…Both suicidal ideation and intent are considered high-risk indicators, and addressing these factors is vital in averting progression to more severe stages. However, the WHO does not officially report data on this subject [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These stages, as mentioned in the text, include periods of help-seeking and may signal underlying mental health issues. Some researchers propose that if these risks can be identified and mitigated, suicide could be categorized as a preventable health concern [5,8,9]. Studies have shown that the risk of suicide escalates in the six months following a self-harm attempt, with the initial month being the most critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have analysed the characteristics of individuals with a presence of suicidal ideation and/or behaviour. From a socio-demographic perspective, risk factors identified include age (middle age and youth; Baca-García et al, 2010;Cabello et al, 2020); gender (women have higher rates of ideation and attempts; Bello & Teruel, 2020) and level of education (lower level of education being associated with greater risk of suicide; Lorant et al, 2005). Contextual risk factors exist, such as a lack of social support or the presence of environmental stress factors (Kaslow et al, 2005;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%